Best Practice Activities in Education of Clean and Healthy Life Behaviors in Children With Special Needs in Facing the Covid-19 Pandemic - Ikram, Muhammad; Nuddin, Andi; Zarkasyi, Rahmat (Indonesian Health Journal, 2022)
Covid-19 is a disease caused by the SARS-CoV virus with general symptoms of acute respiratory tract disorders, both mild and severeThis study aims to determine the level of knowledge and attitudes towards children with special needs in complying with health protocols in Education about clean and healthy living behaviour in preventing covid 19 at SLBN 1 Parepare. This study used a quasi-experimental one-group pretest-posttest design. The sample consisted of several students at SLBN 1 Parepare. The sample was divided into two groups, namely the experimental group, as many as 37 and the control group, as many as 36. Sampling was used using the total sampling method for the population. Data analysis using the Mann test. The results showed that knowledge scores increased by after being given Education on clean and healthy living behaviours 2.19, while attitudes increased after being given Education on clean and healthy behaviours by 4.39. This study concludes that there is an effect of best practice activities on clean and healthy living behaviour with browser media on increasing knowledge (p = 0.000) and attitudes (p = 0.000) of children with special needs, for the school there should be special lessons every month regarding Education about clean and healthy living behaviour in complying with the covid 19 prevention health protocol